THE INFLUENCE OF USING INSTAGRAM SOCIAL MEDIA AND LEARNING CREATIVITY ON STUDENT LEARNING OUTCOMES MAJORING IN OFFICE MANAGEMENT AND BUSINESS SERVICES AT SMK NEGERI JAKARTA TIMUR - Syalsabila, Daffa; Sumiati, Ati; Adha, Maulana Amirul (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research was conducted at SMK Negeri East Jakarta to determine the effect of Instagram Social Media and Learning Creativity on Learning Outcomes with a survey method using a questionnaire as a research instrument. The data used in this study used quantitative data using path analysis. The data analysis technique in this study used the SmartPLS application. The population of this study is class XI MPLB students at SMK Negeri 48 Jakarta, SMK Negeri 10 Jakarta and SMK Negeri 51 Jakarta, totaling 144 students. The sample used was 106 students. The used of a scale in this study is a Likert scale with the data analysis used is Structural Equational Modeling-Partial Least Square (SEM-PLS) for the software used SmartPLS version 3.29. The results of this study are that there is a positive and significant influence between Instagram Social Media variables on student Learning Creativity followed by t-statistics, namely 8.819> 1.662, and has a pvalue of 0.000 <0.05. There is a positive and significant influence between Instagram Social Media variables on Learning Outcomes with t-statistics of 6.290 > 1.662, and has a p-value of 0.000 < 0.05. There is a positive and significant influence between the Learning Creativity variable and Learning Outcomes with t-statistics, namely 5.505> 1.662, and has a p-value of 0.000 <0.05, and there is a positive and significant influence between the Instagram Social Media variable on Learning Outcomes through Learning Creativity.